Impacts of Indoxyl Sulfate and p-Cresol Sulfate on Chronic Kidney Disease and Mitigating Effects of AST-120 - Wen-Chih Liu; Yasuhiko Tomino; Kuo-Cheng Lu (Toxins, 2018)
Uremic toxins, such as indoxyl sulfate (IS) and p-cresol, or p-cresyl sulfate (PCS), are markedly accumulated in the organs of chronic kidney disease (CKD) patients. These toxins can induce inflammatory reactions and enhance oxidative stress, prompting glomerular sclerosis and interstitial fibrosis, to aggravate the decline of renal function. Consequently, uremic toxins play an important role in the worsening of renal and cardiovascular functions. Furthermore, they destroy the quantity and quality of bone. Oral sorbent AST-120 reduces serum levels of uremic toxins in CKD patients by adsorbing the precursors of IS and PCS generated by amino acid metabolism in the intestine. Accordingly, AST-120 decreases the serum IS levels and reduces the production of reactive oxygen species by endothelial cells, to impede the subsequent oxidative stress. This slows the progression of cardiovascular and renal diseases and improves bone metabolism in CKD patients. Although large-scale studies showed no obvious benefits from adding AST-120 to the standard therapy for CKD patients, subsequent sporadic studies may support its use. This article summarizes the mechanisms of the uremic toxins, IS, and PCS, and discusses the multiple effects of AST-120 in CKD patients.